Comparison of a basic lung scanning protocol against formally reported chest x‐ray in the diagnosis of pulmonary oedema. Issue 4 (November 2013) - Baker, Kylie; Mitchell, Geoffrey; Thompson, Angus G; Stieler, Geoffrey
Abstract: Introduction : Brief lung scan protocols have been recommended as a useful adjunct to identify pulmonary oedema in the breathless elderly patient. Some papers quote diagnostic accuracies above that of chest x‐ray. Method : We recruited a prospective convenience sample of patients over sixty years of age reporting any breathlessness on presentation to the emergency department. Those who received both bedside lung scan and chest x‐ray later had their case notes audited by an expert cardiologist for the cause of their breathlessness at presentation. Admission diagnosis was also extracted. Results : 204 comparative data sets were collected. Compared with cardiologist chart review, delayed expert radiology report had a diagnostic accuracy of 92.2% (95%CI 87.6 to 95.1). Bedside interpretation of lung scan protocol had a diagnostic accuracy of 85.3% (95%CI 79.8 to 89.5). The difference of 6.9% between the two accuracy measures was significant (95%CI 0.69 to 13.1). Admission diagnosis accuracy, which encompasses inexpert x‐ray interpretation was 70.2%(95%CI 62.9 to 76.6), significantly less than either lung scan or expert chest x‐ray report. Conclusion : For identifying heart failure in breathless patients, urgent chest x‐ray with delayed formal report has not been shown to be redundant. Basic lung scan protocols should not yet replace chest x‐ray, but may be more reliable in the interim than inexpert clinician interpretation of chest x‐rays.